2001
DOI: 10.1034/j.1600-0501.2001.120507.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed doses from spiral CT and conventional spiral tomography: a phantom vs. cadaver study

Abstract: For several radiological examinations, a clinician can select between conventional and spiral computed tomography. Using both techniques, this study aimed at evaluating the difference in absorbed doses when examining a single lateral jaw segment in a human cadaver head and Rando phantom. The present study involved the placement of thermoluminescent dosimeter (TLD) chips (GR-200) in the thyroid gland, and bilaterally, in the parotid and submandibular glands and the lenses of the eyes in both a human cadaver and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The radiation exposure of additional radiological examinations such as CT is the subject of debate because of the associated theoretical morbidity (Brenner et al, 2001). Especially in the paediatric age group, where it may increase the risk of a significantly higher mutation rate (Frederiksen et al, 1995;Bou Serhal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The radiation exposure of additional radiological examinations such as CT is the subject of debate because of the associated theoretical morbidity (Brenner et al, 2001). Especially in the paediatric age group, where it may increase the risk of a significantly higher mutation rate (Frederiksen et al, 1995;Bou Serhal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bou Serhal et al (2001) (13) found that for spiral tomography in the maxilla, organ doses for both parotid glands were most elevated, and average doses per Avicenna J Dent Res. 2016; 8(4):e24431.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the greatest individual organ doses for any examination are in the salivary tissue (9). Some previous studies have measured the absorbed doses of the radiosensitive organs of the head and neck during imaging modalities (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…CT was chosen for cases of full rehabilitation of the lower jaw. 26,27 Eighteen patients were examined by PAN allowing measurements of all 22 sites. Eight sites in ®ve patients were examined by ST and eight in seven patients by CT. No radiographic examinations supplementary to the standards were required for this study and all examinations formed a part of a routine clinical protocol.…”
Section: Methodsmentioning
confidence: 99%